Silica Exposure Differentially Modulates Autoimmunity in Lupus Strains and Autoantibody Transgenic Mice - Foster, Mary H.; Ord, Jeffrey R.; Zhao, Emma J.; Birukova, Anastasiya; Fee, Lanette; Korte, Francesca M.; Asfaw, Yohannes G.; Roggli, Victor L.; Ghio, Andrew J.; Tighe, Robert M.; Clark, Amy G. (Frontiers in Immunology, 2019)
Inhalational exposure to crystalline silica is linked to several debilitating systemic autoimmune diseases characterized by a prominent humoral immune component, but the mechanisms by which silica induces autoantibodies is poorly understood. To better understand how silica lung exposure breaks B cell tolerance and unleashes autoreactive B cells, we exposed both wildtype mice of healthy C57BL/6 and lupus-prone BXSB, MRL, and NZB strains and mice carrying an autoantibody transgene on each of these backgrounds to instilled silica or vehicle and monitored lung injury, autoimmunity, and B cell fate. Silica exposure induced lung damage and pulmonary lymphoid aggregates in all strains, including in genetically diverse backgrounds and in autoantibody transgenic models. In wildtype mice strain differences were observed in specificity of autoantibodies and site of enhanced autoantibody production, consistent with genetic modulation of the autoimmune response to silica. The unique autoantibody transgene reporter system permitted the in vivo fate of autoreactive B cells and tolerance mechanisms to be tracked directly, and demonstrated the presence of transgenic B cells and antibody in pulmonary lymphoid aggregates and bronchoalveolar lavage fluid, respectively, as well as in spleen and serum. Nonetheless, B cell enumeration and transgenic antibody quantitation indicated that B cell deletion and anergy were intact in the different genetic backgrounds. Thus, silica exposure sufficient to induce substantial lung immunopathology did not overtly disrupt central B cell tolerance, even when superimposed on autoimmune genetic susceptibility. This suggests that silica exposure subverts tolerance at alternative checkpoints, such as regulatory cells or follicle entry, or requires additional interactions or co-exposures to induce loss of tolerance. This possibility is supported by results of differentiation assays that demonstrated transgenic autoantibodies in supernatants of Toll-like receptor (TLR)7/TLR9-stimulated splenocytes harvested from silica-exposed, but not vehicle-exposed, C57BL/6 mice. This suggests that lung injury induced by silica exposure has systemic effects that subtly alter autoreactive B cell regulation, possibly modulating B cell anergy, and that can be unmasked by superimposed exposure to TLR ligands or other immunostimulants.